Efficient titanium nitride/titanium oxide composite photoanodes for dye-sensitized solar cells and water splitting1. Issue 8 (28th February 2015) - Li, Chun-Ting; Li, Sie-Rong; Chang, Ling-Yu; Lee, Chuan-Pei; Chen, Pei-Yu; Sun, Shih-Sheng; Lin, Jiang-Jen; Vittal, R.; Ho, Kuo-Chuan
<x xml:space="preserve">Abstract</x> Efficient titanium nitride/titanium oxide composite photoanode separately renders good performance to a dye-sensitized solar cell and a water splitting electrochemical device.